2020
DOI: 10.1038/s41396-020-0642-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of viruses in a tapeworm: phylogenetic position, vertical transmission, and transmission to the parasitized host

Abstract: Parasitic flatworms (Neodermata) infect all vertebrates and represent a significant health and economic burden worldwide due to the debilitating diseases they cause. This study sheds light for the first time into the virome of a tapeworm by describing six novel RNA virus candidate species associated with Schistocephalus solidus, including three negative-strand RNA viruses (order Jingchuvirales, Mononegavirales, and Bunyavirales) and three double-stranded RNA viruses. Using in vitro culture of S. solidus, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…Given that fitness-based selection and phenotypic plasticity are connected to genome size [18][19][20] , this expanded genome may be related to its strikingly wide host range. Notably, the wide endogenization of various viral genomes into the tapeworm genome suggests previous viral infections 21 , consistent with a recent study that identified six novel RNA viruses that infect the tapeworm Schistocephalus solidus 22 . Importantly, the study proved that the S. solidus rhabdovirus can be transmitted from tapeworms to their parasitized hosts, impacting S. solidus-host interactions.…”
Section: Discussionsupporting
confidence: 84%
“…Given that fitness-based selection and phenotypic plasticity are connected to genome size [18][19][20] , this expanded genome may be related to its strikingly wide host range. Notably, the wide endogenization of various viral genomes into the tapeworm genome suggests previous viral infections 21 , consistent with a recent study that identified six novel RNA viruses that infect the tapeworm Schistocephalus solidus 22 . Importantly, the study proved that the S. solidus rhabdovirus can be transmitted from tapeworms to their parasitized hosts, impacting S. solidus-host interactions.…”
Section: Discussionsupporting
confidence: 84%
“…We also provide evidence that some of the parasite-associated bacteria contribute to modulating the host immune system. Recently, we also discovered that viruses are associated with S. solidus and that some of these are transmitted to parasitized hosts, which means that viruses could also impact the host immune response [98]. Further studies are needed to test whether S. solidus relies on these microbes for infection, or whether they are detrimental for the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Asterisks indicate main branches for which bootstrap support was <0.7. The dataset used for the phylogeny includes all currently assigned bunyavirus families [ 1 ], the grouping of which is broadly in line with that presented in a recently published tree [ 25 ]. The numbered, black lines in the figure denote bunyavirus species currently not assigned to a family [Wuhan spider virus ( 1 ), Laurel lake virus ( 2 ), Hubei blood fluke virus 2 ( 3 ), Hubei blood fluke virus 1 ( 4 ), Mothra virus ( 5 ), Shistocephalus solidus bunya-like virus ( 6 )].…”
Section: Introductionmentioning
confidence: 99%